Pop-up book media integrated Islamic values and Pancasila to foster motivation and care - Muzayanati, Apriliyanti; Nugraheni, Aninditya Sri (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
This study aims to motivate students in learning and instill an attitude of environmental care integrated with Islamic values and Pancasila. The research and Development (R&D) method used the ADDIE model, a type of research method pre-experimental design (nondesign) one group pretest-postest with non-parametric. The subjects of the study were 21 fourth grade students of MIN 4 Madiun. Data collection techniques consisted of observations, interviews, documentation, and questionnaires. The data then analyzed quantitatively. The results shows that first, a product has been produced with an ADDIE development model in the form of a Pop-up book Media integrated with Islam and Pancasila values. Second, eligibility results have been obtained from several experts, including material experts, got an average of 95.5%, and language validation scores obtained 88.6%.  Media validation received a score of 95.4%, teacher response 88.3%, and student response to media got a score of 95.8%. So it can be concluded that this Pop-up book media is worth using. Third, there is a positive influence on students after using Pop-up book media.